1997
DOI: 10.2165/00003495-199753020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine

Abstract: Olanzapine is a thienobenzodiazepine derivative which displays efficacy in patients with schizophrenia and related psychoses. It has structural and pharmacological properties resembling those of the atypical antipsychotic clozapine and an improved tolerability profile compared with the classical antipsychotic haloperidol. In several large, well controlled trials in patients with schizophrenia or related psychoses, olanzapine generally 5 to 20 mg/day was at least as effective as haloperidol (5 to 20mg) and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(66 citation statements)
references
References 36 publications
1
62
0
1
Order By: Relevance
“…On the other hand, olanzapine has a favorable sidee¤ect proÞle with minimal extrapyramidal symptoms (EPS), prolactin elevation, sedation induction, and anticholinergic symptoms and no evidence of hematotoxicity (Beasley et al 1996;Fulton and Goa 1997). Thus, olanzapine is believed to be a Þrst-line drug for the treatment of schizophrenia (Meltzer and Fibiger 1996), since the clinical use of the prototype atypical antipsychotic clozapine is limited due to the incidence of agranulocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, olanzapine has a favorable sidee¤ect proÞle with minimal extrapyramidal symptoms (EPS), prolactin elevation, sedation induction, and anticholinergic symptoms and no evidence of hematotoxicity (Beasley et al 1996;Fulton and Goa 1997). Thus, olanzapine is believed to be a Þrst-line drug for the treatment of schizophrenia (Meltzer and Fibiger 1996), since the clinical use of the prototype atypical antipsychotic clozapine is limited due to the incidence of agranulocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…22) Indeed, clozapine is generally administered in the range of 200-900 mg/d, while for olanzapine the usual dose is 10-20 mg/d. Consequently, the low therapeutic plasma concentrations of olanzapine (0.03-0.1 mmol/ l) 23,24) compared to those of clozapine (0.2-1.6 mmol/l) 25) might explain why olanzapine is not frequently associated with agranulocytosis in humans. 820 Vol.…”
Section: Discussionmentioning
confidence: 99%
“…7) Interestingly, despite the structural similarity between clozapine and olanzapine, no cases of agranulocytosis have been reported with the clinical use of olanzapine. 8) Recently, we reported that Y-931 (8-fluoro-12-(4-methylpiperazin-1-yl)-6H- [1]benzothieno [2,3-b] [1,5]benzodiazepine), [9][10][11] which was developed in our laboratory, showed a pattern of interaction with various neurotransmitter receptors similar to that of clozapine. In addition, Y-931 did not cause catalepsy (a correlate of EPS), despite its potent antagonistic activity of apomorphine-induced hyperlocomotion or conditioned avoidance response (a correlate of antipsychotic effects).…”
mentioning
confidence: 99%
“…Olanzapine is a new antipsychotic drug, one of the socalled atypical antipsychotics, with a favorable tolerance profile, and it has been shown to be effective against both the positive and negative symptoms of schizophrenia [29]. In addition, it has been suggested that olanzapine should be considered as first-choice therapy in the first psychotic episode because of its advantages in both safety and efficacy [30].…”
Section: Introductionmentioning
confidence: 99%